Grenada : Staff Report for the 2016 Article IV Consultation, Fourth Review Under the Extended Credit Facility, Request for Waiver of Non-Observance of a Performance Criterion, Request for Modification of a Performance Criterion and Financing Assurances Review-Press Release and Staff Report. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2016)
This paper features Grenada's request for waiver of non-observance of a performance criterion, request for modification of a performance criterion, and financing assurances review. The arrangement was approved on June 26, 2014, and the third review was completed on November 25, 2015. Grenada's comprehensive public debt restructuring is nearing completion. The debt exchange with Grenada's largest private creditor group was implemented, and an agreement reached with Paris Club creditors. Discussions focused on completing the programmed fiscal consolidation, finalizing reforms to Grenada's fiscal policy framework, and improving competitiveness and growth prospects. Staff proposes to refine the structural benchmark on public sector modernization to focus specifically on public wage bill management.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet